Abiotic Stress Effects on Sorghum Leaf Dhurrin and Soluble Sugar Contents throughout Plant Development. Issue 4 (21st June 2018) - Emendack, Yves; Burke, John; Laza, Haydee; Sanchez, Jake; Hayes, Chad
Abstract : Although cyanogenic glucosides are considered to play important roles in plant growth, development, and resistance against abiotic and biotic stresses, their presence in high concentrations in feed and food can be fatal to animals and humans. Sorghum [ Sorghum bicolor (L.) Moench] is cyanogenic, and the cyanide potential varies with environmental factors, management, and genetic background. Acyanogenic lines have not been identified to date in natural collections. Although the variability of cyanide potentials in seedlings and leaves of plants at early growth stages has been highly researched, few works have looked beyond these stages, especially under variable environmental factors such as water deficit stress. Here, we evaluated 40 diverse sorghum lines for leaf dhurrin and soluble sugar content at various crop developmental stages and variable water availability. Five lines were identified with little‐to‐very low leaf dhurrin content across developmental stages and water availability. Leaves of 30‐d‐old sorghum plants had less cyanide potential than at later stages. A brief preflowering water stress, imposed at booting to flowering, decreased leaf dhurrin and soluble sugar contents, whereas a brief postflowering water stress or prolonged preflowering water stress increased dhurrin and soluble sugar contents. Rapid and efficient screening of dhurrin levels within existing sorghum germplasms could lead to the identification of additional lines with very low to nondetectable dhurrin levels, which will have an enormous impact on sorghum breeding and increase the agronomic value of the sorghum crop.